Geopolitical Labyrinths of the Three Guianas in the Regional Cooperation and Integration Processes - Gutemberg de Vilhena Silva; Stéphane Granger; Bruna Brito Bastos (Revista Brasileira de Política Internacional, 2023)
Abstract The purpose of the article is to analyze to what extent regional cooperation and integration strategies helped strengthen Guyana, Suriname and French Guiana in international and regional geopolitics. Through bibliographical and documentary analysis, combined with field trips, a schematic periodization of regionalism processes is outlined to conclude that historical, geographical and cultural factors position these Guianas as an interface between different regions. Despite various challenges, Guyana and Suriname’s presence in regional blocs intensify their political and economic ties and the French administration has expanded its outreach, collaborating with neighbors on common issues such as environment, security and infrastructure.